Keterlibatan Corporate Social Responsibility dalam Interaksi Antara Kinerja Lingkungan dan Kinerja Keuangan: Literature Review - Nadia Safitri; Jedli Saputra; Rina Yuniarti (Journal of Creative Student Research, 2025)
This study aims to analyze the role of Corporate Social Responsibility (CSR) in linking environmental performance with the company's financial performance. The study was conducted through a literature review of national and international journal articles published between 2020 and 2025. The articles analyzed discuss the topics of environmental performance, CSR, and financial performance. The results of the study show that environmental performance can have a positive impact on a company's financial performance, especially through increased efficiency, risk reduction, and the creation of new business opportunities. CSR acts as a connecting factor that strengthens these relationships by increasing reputation, legitimacy, and public trust in the company. However, the effectiveness of CSR is highly dependent on the implementation strategy carried out and the characteristics of the company, so the results of the study show significant variations. Thus, this study confirms the importance of integrating CSR in the company's business strategy, not only as a form of social responsibility, but also as an instrument to strengthen the relationship between environmental sustainability and financial performance. These findings are expected to contribute to the development of corporate policies that are more oriented towards sustainability and long-term competitiveness.